Penurunan Timbal (Pb) Air Laut Pulau Bengkalis Menggunakan Tanah Lempung Dengan Metode Penukar Ion Pada Variasi Tinggi Unggun Dan Debit Aliran - Romadona, Syahri; Elystia, Shinta; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The lack of clean water Sources in the regency of Bengkalis create communities that are the island's shortage of clean water. Moreover, during the dry season, services of PDAM Bengkalis was only able to supply about 10% of the number of existing communities. While Bengkalis island has abundant sea water availability. The purpose of research is to reduce the concentrations of Pb and pH as on the parameter using the method of ion exchange support using column height 1.2 m in diameter 2 inches of clays as well as Kulim size -10+15 mesh that has been on activation by using the HCI. A variation was used in this study is bed hight of 40 cm, 80 cm and 120 cm with discharge flow 80 ml/min, 100 ml/min, and 120 ml/min. Results of the analysis of effluents obtained efficiency for metal Pb is in the range of 41,44% - 89,35%. Metal concentrations of pb with the best reduction of 0,024 mg/L at bed hight variation 80 cm with discharge flow 80 ml/min and the pH from 8,5 to be 7,3. These concentrations already meets the quality of the raw water supply based on PERMENKES416/MENKES/PER/IX/1990. Cation Exchange Capacity (CEC) values obtained at the best efficiency of 78.6 Meq/100 gr with most types of minerals contained in the clay Kulim is a montmorilonit.Keywords: Bed Hight, Clay, Discharge Flow , Ion Exchange, Sea Water Bengkalis